The societal dimensions of political development in Yemen and its components - Al Shamsi, Salem Mohammed Saeed (Journal of Humanities & Social Sciences, 2017)
The importance of this study is that it seeks to analyze Community structure of reality of the process of political development in Yemen with its multiple dimensions economically, socially, politically and culturally, to know the mutual influence between these dimensions and variables, considering that this interaction is the natural entrance to creating comprehensive community development, because development cannot be achieved on one side without the rest of the other which is called the dialectical relationship between Epitaxial construction and infrastructure of the community. This is what the study seeks to shed light on through the scientific analysis of this interactive relationship. The main objectives of the study are to highlight the importance of societal reality as the social carrier of political development, as society is the area in which, through which and for which, politics is practiced. The study also aims at identifying the obstacles to political development in Yemen. The most important conclusion of the study is that the process of political transformation in Yemen towards political pluralism and multi-party which occurred in 1990, was in the context of a traditional tribal community reality, one of most important of its characteristics is that power is a source of wealth, strength and prestige in society. This peculiarity intersects completely with the culture of political and party pluralism as a modern concept on the one hand, and the necessity of stability of the political system and the availability of objective conditions for the growth and development of democracy, as the most important social mechanisms to solve the problem of community decision-making among groups where conflict of interests and other political and intellectual beliefs on the other hand . In this sense, the possibility of political development based on multi-partyism for the peaceful transfer of power in a traditional sociological reality with its various dimensions seems weak in practice. This requires the search for a mechanism that will make multiparty and political a means of modernization and development rather than fighting and rivalry which deepens underdevelopment, and this requires the participation of all in the cause of political advancement and development as an independent variable leading to social development, to the extent that social reality becomes the independent variable which positively affects the process of political evolution as a dependent variable, based on successful human experiences in the process of transition from the traditional social reality to the state of modernity and contemporary which is embodied by the existence of a modern civil state based on political and civil institutions represented by political parties and civil society organizations which is called good governance based on the rule of law, equality and social justice. Hence, it is possible to talk about the achievement of the process of political development quantitatively and quantitatively, which is the situation we miss in Yemen, which led to the absence of political vision and the lack of clarity of the objectives of democratic practices based on the right to diversity of political and intellectual as an expression of a similar diversity in social construction as an inevitable fact that cannot be denied or ignored.